Social determinants and follow-up care after emergency department discharge for traumatic intracranial hemorrhage - Meghan M. Dillan; Joseph Piktel; Adam Perzynski; Mary Jo Roach; Kristen K. Curtis; Yasir Tarabichi; Lance Wilson; Michael L. Kelly (Heliyon)
Background: Traumatic brain injury (TBI) is a multifaceted condition associated with occupational, social, physical, cognitive, academic, and economic burdens. Mild TBI including traumatic intracranial hemorrhage (tICH), is commonly discharged from the emergency department (ED). Despite the complexity of factors contributing to TBI outcomes, patient education and comprehensive follow-up plans are frequently lacking. We examined health trajectories, recidivism, and follow-up patterns of patients discharged from the ED with tICH to identify opportunities to improve care. Methods: We conducted an IRB approved retrospective observational study at a large urban Level 1 trauma center from January 2017 to July 2022. We identified patients (n = 117) discharged from the ED with acute tICH, using IDC 9/10 codes and confirmed by imaging review. Exclusions were hospital admission, chronic ICH, and age under 18. The primary outcome was an ED-revisit within 180 days. Secondary outcomes included any return TBI visit, scheduled specialty TBI provider visit, and post-TBI mental health disorder diagnoses. Age, gender, race, ethnicity, pre-TBI mental health disorders, and socioeconomic status (SES) were analyzed. SES was measured using area deprivation index (ADI). Statistical analysis was performed with logistic regression and Chi-squared tests. Results: The average age of enrolled patients was 53 ± 20 years with 39 % female, 26 % Black, 69 % White, and 6 % Hispanic. Overall follow-up rates were low, with 49 % of patients having at least one scheduled follow-up visit within 180 days. Only 16 % of Black patients saw a TBI specialty provider visit within 180 days compared to 36 % of White patients (p = .03). ED recidivism rate was 18 %, with 25 % of patients overall having an unscheduled TBI visit. Lower SES was a significant predictor of any TBI revisit (OR 1.39, CI 1.06, 1.82). New mental health diagnoses following tICH occurred in 15 % of patients; depression and anxiety were most common. There was no association between SES, age, gender, race, or ethnicity and new mental health diagnoses. Conclusion: We observed racial and SES differences in follow-up care from the ED for patients with TBI. Individualized discharge planning and formulation of care pathways that account for the mental health and social needs of all patients may improve long-term outcomes. Further understanding of health disparities present in ED TBI care is needed.